KETERAMPILAN BERBICARA BAHASA INGGRIS DAN HUBUNGANNYA TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA CALON GURU MELALUI PROMOSI POTENSI DAERAH - Rochyani Lestiyanawati; Luluk Alawiyah (STKIP Subang, 2026)
The purpose of this study was to determine the effectiveness of the regional potential promotion approach in improving the English speaking skills of prospective teacher students and whether there was a relationship between the improvement in English speaking skills that occurred with students' interest in entrepreneurship. This study was a quantitative study with a True Experimental Design model of one group pretest-posttest design conducted on a population of 76 second-semester students divided into three classes at a Private Islamic University in Central Java, Indonesia. Samples of two classes were taken by random sampling, data collection using English speaking skills assessment instruments and an entrepreneurial interest questionnaire with data analysis including homogeneity test, normality test, average difference test, improvement test and correlation test. The results of the study showed a large t-value of 5.71 with a t-table of 2.003 (α 0.05), an N-Gain value of 0.35 with moderate improvement criteria in the experimental class and a control class of 0.039 with low improvement criteria, the results of the Pearson Product Moment value obtained were 0.73 with strong relationship criteria.